THE APPLICATION OF CONCEPT SENTENCE COOPERATIVE MODEL USING PHOTOGRAPH IMAGE IN IMPROVING WRITING SKILLS OF ESSAY FOR THE FOURTH GRADE STUDENTS OF SD NEGERI 2 SEMANDING IN THE ACADEMIC YEAR OF 2015/2016 - Haini, Naeli Afri (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Concept Sentence Cooperative Model Using Photograph Image in Improving Writing Skills of Essay for the Fourth Grade Students of Elementary Schools. The objectives of this research are: (1) to describe the steps on the application of Concept Sentence model using photograph image to improve writing skills of essay for the fourth grade students of elementary schools. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection. Subjects of the research were 25 students of the fourth grade of SD Negeri 2 Semanding.The conclusion of this research is the application steps of Concept Sentence cooperative model using photograph image, namely: (a) deliver the learning objectives, (b) deliver the learning materials through Concept Sentence model using photograph image, (c) divide groups into four students heterogeneously, (d) provide some keywords and a photograph image based on materials, (e) each groups is instructed to make some sentences using at least four keywords on each sentence and according to the photograph image, (f) present the results of group discussion in front of the class and students discuss again guided by the teacher, (g) conclusion; moreover the application of Concept Sentence cooperative model using photograph image can improve writing skills of essay for the fourth grade students. It was proven by the increase of percentage of students? learning outcomes in the first cycle 60%, in the second cycle 78%, and in the third cycle 88%.Keywords: Concept Sentence, photograph image, writing skills